2022
DOI: 10.3389/fonc.2022.946113
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of “sandwich” chemoradiotherapy compared with chemotherapy alone for the adjuvant treatment of FIGO stage III endometrial cancer

Abstract: ObjectiveTo analyze and compare outcomes of adjuvant chemoradiotherapy in patients with International Federation of Gynecology and Obstetrics (FIGO) stage III endometrial cancer (EC) patients using the “Sandwich” sequence and chemotherapy (CT) alone.MethodsFrom, 2005 to, 2019, we retrospectively reviewed 80 patients with FIGO stage III EC who received treatment at our institute. We analyzed 66 patients who had undergone complete surgical staging followed by adjuvant treatment with sandwich chemoradiotherapy (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In 2022, Wang et al published a retrospective study on 66 patients who underwent complete surgical staging followed by sandwich chemoradiotherapy (39 patients) or CT alone (27 patients). They found that the sandwich schedule was a positive predictor of 5-year DSS ( p = 0.029), even if it was associated with higher acute hematologic toxicity than the CT-alone arm [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Wang et al published a retrospective study on 66 patients who underwent complete surgical staging followed by sandwich chemoradiotherapy (39 patients) or CT alone (27 patients). They found that the sandwich schedule was a positive predictor of 5-year DSS ( p = 0.029), even if it was associated with higher acute hematologic toxicity than the CT-alone arm [ 33 ].…”
Section: Discussionmentioning
confidence: 99%